Some aspects of the approach to modelling assignments of the means for the tasks in municipal services companies - Izdebski, Mariusz; Jacyna, Marianna (Management and Administration Journal, 2023)
In this article the assignment problem of vehicles to tasks in municipal services companies in the context of designating the minimum routes of vehicles was presented. The mathematical model of the assignment problem was developed, and proposed a method for solving the assignment problem in municipal services companies. The method consists of two stages i.e. the stage of designating the minimum route consisting of all tasks and the stage of designating individual routes for each vehicle. In the light of considerations indicating individual routes we designate the tasks to the implementation, which is the equivalent of solving the assignment problem. The genetic algorithm for solving the optimization problem presented in the first stage of the method was proposed. Verification of this algorithm confirmed its effectiveness.